The effect of the analogical thinking strategy in teaching some defensive and offensive principles of handball to students - Dawood, L. M. J.; Mushin, H. A.; Habib, K. (Proximus Journal of Sports Science and Physical Education, 2024)
One of the modern strategies that works within the principles and ideas of constructivist theory, which is considered a teaching approach that enables teachers to teach their students in a way that is described as constructivist, is the analogical thinking strategy, which works to link information, observations, and previous experiences with new information and assignments that are similar, different, or They are similar to each other in theory or application.From all of the above, the importance of research lies in experimenting with the analogical thinking strategy, which enables, through the sequence of its steps, the creation and representation of concepts and variables (similarities and differences) and the strengthening of students` potentials and abilities in building knowledge, relying on their stored knowledge environment to reach common solutions. Or individually by students to achieve the goal of the educational unitThe problem of the research is how the teacher can establish a method of thinking about analogical knowledge and the method of obtaining it, reformulating it, and building it in the theoretical and practical aspects through an organized set of facts, concepts, and instructions, and drawing a map of the extent of similarity and difference in thinking and performance. Arriving at solutions based on the knowledge environment he possesses to achieve the goal or goals of the educational unit and not through automatic learning by the teacher. The aim of the research was to prepare an educational curriculum according to the analogical thinking strategy in teaching some offensive and defensive principles of handball to students. Also identifying the effect of the analogical thinking strategy using physical modeling and the method used by the teacher (Al-Amri) in teaching some defensive and offensive principles of handball to students.The researcher used the experimental method (two equal groups) because "the experiment searches for the cause and how it occurs, and the researcher addresses the variables of the phenomenon by studying the causes of a sample of third-year students in the College of Physical Education and Sports Sciences at the University of Basra for the academic year (2022-2023) for study." Al-Sabah (305) students. The most important conclusions were that the educational curriculum prepared by the researcher had a positiveimpact on all the variables investigated, as well as the approach, but the best was the curriculum prepared by the teacher.The educational units provided active participation and departure from the familiar by comparing similarities and contrasts and arriving at applied solutions.